A climate adaptation policy, incomplete but persistent:: the case of the Pastoral Zone of CEZIET of Samorogouan (Burkina Faso) - Hochet, Peter; Guissou, Charles (Sustainability in Debate, 2010)
In Samorogouan (Burkina Faso), pastoral migration has been planned by the World Bank through a project titled « Projet d’Élevage Ouest Volta (PEOV) ». With the agreement of the local authorities, the project defines a large territory (125.000 hectares) dedicated to ranching and to the settlement of the pastoralists who had fled the region during the droughts of the 70s. The project was cancelled in 1984, during the Sankarist revolution. Nowadays, the pastoral zone is threatened by clearance and by various conflicts between settled pastoralists, Justice, the local administration and farmers.